Does Ethics Sell? Analyzing Sharia Marketing on Banking Customer Loyalty (IAIN Kudus, 2025)
This study examines the effect of the Sharia marketing mix on customer loyalty in Islamic banking. Using a quantitative approach, data were collected through an online questionnaire distributed to 295 customers of Bank Syariah Indonesia (BSI) in Kudus Regency. The research model incorporates five dimensions of the Sharia marketing mix—product, price, promotion, place, and people—and analyzes their influence on customer loyalty using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. The results indicate that all Sharia marketing mix variables significantly affect customer loyalty. Product, price, promotion, and place have positive and significant effects on loyalty, suggesting that Sharia-compliant products, fair and transparent pricing, effective promotional communication, and easy access to banking services play crucial roles in strengthening long-term customer relationships. Among these variables, promotion emerges as the most dominant factor influencing loyalty. Interestingly, the people (employees) variable shows a negative and significant effect on customer loyalty, indicating a potential service gap between customer expectations and actual employee performance, particularly in the context of increasingly digitalized Islamic banking services. Overall, the findings demonstrate that customer loyalty in Islamic banking is shaped not only by adherence to Sharia principles but also by the effectiveness of marketing mix implementation and the quality of service experiences perceived by customers. This study contributes to the literature by highlighting the complex role of employees in Islamic banking and underscores the importance of enhancing employee competence and service quality to build sustainable customer loyalty.